OPTIMIZATION THE PERFOMANCE OF PHOTOVOLTAIC PANELS FOR CITRONELLA OIL DISTILLATION - Safitri, Nelly; Suprihardi; Ridwan; Rihayat, Teuku; Aidy, Nurhanifa; Setiawati, Een (International Journal of Research -GRANTHAALAYAH, 2022)
Photovoltaic system is a module that is used to absorb heat that is exposed to sunlight which is converted into electrical energy. The purpose of this research is to use a solar panel with a capacity of 100 wp to absorb heat which is converted into electrical energy as much as 100 watts/hour which is later expected to be a substitute for conventional electricity which will be used for the refining process. The treatment was carried out by varying the drying time of citronella leaves 0, 1, 2 and 3 days and the time for citronella oil distillation operation for 1.5, 3, 4.5 and 6 hours. By using a solar cell that has a capacity of 100 wp for 6 hours a day when exposed to sunlight it can produce power of 600 watts / day. Testing of distilled citronella oil using the photovoltaic method, the best density was obtained at a distillation time of 1.5 hours with a drying time of 1 day of 0.8889 kg/cm3. Refractive index testing, drying time of 1 day with a distillation time of 1.5 hours the value obtained is 1.4655. The more the chain components with the oxygen group are also distilled, the density of the oil will increase so that the incoming light is more difficult to refract. The yield of lemongrass oil at a drying time of 3 days with a distillation time of 6 hours the value obtained was 2.30%. Drying and withering the amount of material that can be distilled per distillation increases, so that the refining of the material in a dry state is more efficient. The best distillation time is 6 hours, this occurs due to the longer a material receives heat, the more evenly distributed the diffusion process causes the distillation process to be more efficient and greatly affects the yield and oil yield.